2006
DOI: 10.1159/000093263
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Apolipoprotein Polymorphism on Brain in Mild Cognitive Impairment: A Voxel-Based Morphometric Study

Abstract: We investigated the effect of apolipoprotein E (ApoE) on the whole brain in 51 individuals with mild cognitive impairment using voxel-based morphometry. Between cases heterozygous for the ApoE Ε4 (n = 15) and those who were ApoE Ε4 noncarriers (n = 28), only the right parahippocampal gyrus, with the entorhinal cortex included, reached the level of statistical significance. In cases homozygous for the Ε4 allele (n = 8) versus noncarriers, the greatest atrophy was located in the right amygdala followed by the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 101 publications
3
9
1
Order By: Relevance
“…VBM provides an automated method to assess structural changes on a whole-brain level. The present study expands upon our previous work [6,7] by investigating differences in brain structure according to the APOE status and later conversion to dementia. We hypothesized that the APOE 4 carriers progressing to dementia would show more brain atrophy than the noncarriers.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…VBM provides an automated method to assess structural changes on a whole-brain level. The present study expands upon our previous work [6,7] by investigating differences in brain structure according to the APOE status and later conversion to dementia. We hypothesized that the APOE 4 carriers progressing to dementia would show more brain atrophy than the noncarriers.…”
Section: Introductionsupporting
confidence: 51%
“…Previous studies have detected MTL atrophy in relation to the APOE 4 allele in healthy controls, and MCI and AD subjects [3][4][5][6] . However, results are inconsistent as regards global brain atrophy as in a previous study, the 4 carriers did not show more global atrophy [3] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3,4 Cross-sectional structural MR imaging studies indicated reduced gray matter in elderly APOE*E4 carriers including healthy controls, subjective memory impairment, mild cognitive impairment (MCI), and AD. [5][6][7][8][9][10][11][12][13][14] In MCI and AD, the APOE*E4-related GM decrease seems to affect areas involved in AD pathology, notably the hippocampus, amygdala, and mesial temporal cortex [14][15][16][17] but also the left occipital, frontal, and anterior cingulate cortices. 14,18 In healthy elderly controls, the APOE*E4 effect on brain structure is less clear.…”
mentioning
confidence: 99%
“…Other findings are in line with this conclusion. There is a strong body of evidence suggesting that 4 carriers with MCI tend to have smaller hippocampi and amygdalae than patients not carrying the 4 allele but having similar demographic characteristics [57][58][59][60]. Other studies have instead reported volumetric loss in 4 carriers extending to other cortical and subcortical areas [61][62][63][64], although some have suggested that non-carriers can cope with a much more pronounced and extensive brain volume loss before manifesting the same level of cognitive disruption [64].…”
Section: Discussionmentioning
confidence: 99%